1997
DOI: 10.1152/ajpregu.1997.272.2.r691
|View full text |Cite
|
Sign up to set email alerts
|

Control of proximal tubule acidification by the endothelium of the peritubular capillaries

Abstract: Guanosine 3',5'-cyclic monophosphate (cGMP), a nitric oxide mediator, stimulates Na+/H+ exchange in brush-border vesicles of the renal cortex. The aim of the present work was to test whether the endothelium of the peritubular capillaries modulated the rate of proximal luminal acidification through the release of endothelium-derived nitric oxide (EDNO). Perfusion of the tubule lumen with dibutyryl cGMP increased net proton flux (J(H)). Two agents that elicit EDNO production, bradykinin (BK) and carbamylcholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…In previous reports, some investigators demonstrated the stimulatory effect of NO on the proximal tubular fluid and Na ϩ transport (3,33,34), whereas others showed the inhibitory effect (10,20,32). The diversity of NO action on the proximal tubular cell might partly be caused by the biphasic action of NO (19,22).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous reports, some investigators demonstrated the stimulatory effect of NO on the proximal tubular fluid and Na ϩ transport (3,33,34), whereas others showed the inhibitory effect (10,20,32). The diversity of NO action on the proximal tubular cell might partly be caused by the biphasic action of NO (19,22).…”
Section: Discussionmentioning
confidence: 97%
“…A study using microperfused rat proximal tubules revealed that an NOS inhibitor suppressed the absorption of Na ϩ and HCO 3 Ϫ , whereas NO donors stimulated it, probably by affecting the apical Na ϩ /H ϩ exchange (33). Furthermore, NOS knockout mice exhibited a defect in the proximal tubular absorption of fluid and HCO 3 Ϫ (34).…”
mentioning
confidence: 99%
“…Indeed, controversy exists about whether NO stimulates or inhibits sodium transport in specific nephron segments. 16 -20 Although several studies indicate that NO inhibits sodium reabsorption, 16,17,20 others have suggested that NO and cGMP stimulate proton flux and sodium and bicarbonate transport in proximal tubule cells 18,19 and that inhibition of NOS increases fractional sodium excretion. 18 The present study was designed to clarify the role of local generation of cGMP in the renal interstitial space in the control of renal sodium excretion.…”
mentioning
confidence: 99%
“…The Na + /H + exchanger localised in the apical membrane of the proximal tubule is regulated by many factors including, among others, RAS (Reilly et al 1995;Saccomani et al 1990), NO⋅ (Amorena and Castro 1997;Manning et al 1997;Wang 1997), andPTH (Bank andAynedjain 1976).…”
Section: Discussionmentioning
confidence: 99%
“…The control of proximal acidification is very complex and depends on many factors including, among others, RAS (Reilly et al 1995), NO (Amorena and Castro 1997;Manning et al 1997;Wang 1997), and parathyroid hormone (PTH) (Bank and Aynedjain 1976). The serum concentration of PTH increases with aging in both humans and rats (Fox 1991;Halloran et al 1996).…”
Section: Introductionmentioning
confidence: 99%